Key Features of Gamma-Delta T-Cell Subsets in Human Diseases and Their Immunotherapeutic Implications - Lawand, Myriam; Déchanet-Merville, Julie; Dieu-Nosjean, Marie-Caroline (Frontiers in Immunology, 2017)
The unique features of gamma delta (γδ) T cells, related to their antigen recognition capacity, their tissue tropism, and their cytotoxic function make these cells ideal candidates that could be targeted to induce durable immunity in the context of different pathologies. In this review, we focus on the main characteristics of human γδ T cell subsets in diseases and the key mechanisms that could be explored to target these cells.